A LINGUACULTURAL STUDY OF VEHICLE NAMES IN THE UZBEK AND ENGLISH LINGUISTIC LANDSCAPES - Ergasheva Baxtiniso (International Journal of Literature and Language Studies, 2026)
This paper investigates the linguacultural characteristics, semantic structures, and sociolinguistic functions of vehicle names within the linguistic landscapes of Uzbekistan and English-speaking countries. By examining 200 vehicle-related names, including official brand models and popular informal car slang, we explore how cultural mentalities, economic realities, and historical narratives shape naming practices. The study utilizes conceptual metaphor theory, semantic field classification, and comparative linguacultural analysis. The results show that while English vehicle naming is highly commercialized and centered around individualist themes of power, freedom, and exploration, the Uzbek informal vehicle landscape is characterized by collectivist values, utility, humor, and domestic zoomorphic metaphors. This study provides a comprehensive framework for understanding the interaction between language, culture, and automotive branding.